Increased Risk of Myofascial Pain Syndrome Among Patients with Insomnia. Issue 8 (11th February 2017) - Lin, Wei-Chen; Shen, Cheng-Che; Tsai, Shih-Jen; Yang, Albert C.
Abstract: Objective.  The aim of this study is to evaluate the risk of developing myofascial pain syndrome among patients diagnosed with insomnia. Methods.  We conducted a population-based longitudinal study of a matched cohort with 7, 895 participants (1, 579 patients with insomnia and 6, 316 controls) who were selected from the Taiwan National Health Insurance Research Database. The patients were observed for a maximum of 10 years to determine the incidence of newly diagnosed myofascial pain syndrome. A Cox regression analysis was performed to identify the risk factors associated with myofascial pain syndrome in patients with insomnia. Results.  During the 10-year follow-up period, 182 insomnia patients (14.9 per 1, 000 person-years) and 379 controls (7.5 per 1, 000 person-years) were diagnosed with myofascial pain syndrome. The incidence risk ratio of myofascial pain syndrome between the insomnia and control patients was 2.00 (95% confidence interval [CI] = 1.67–2.38, P  < 0.001). After adjusting for age, sex, monthly income, urbanization, and comorbidities, the insomnia patients were 1.93 times more likely to develop myofascial pain syndrome (95% CI = 1.62–2.31, P  < .001) than the control patients. Malignant neoplasm (hazard ratio = 3.08) and living in urban areas (hazard ratio = 3.05) were identified as independent risk factors for myofascial pain syndrome in patients with insomnia. Conclusions. Patients with insomnia had a higher risk of developing myofascial pain syndrome than controls. This study adds to the understanding of the complex relationship between sleep disturbance and pain.